Exploring consumer single-use plastic reduction behaviour : a conceptual framework - Farah Murni Merican; Syuhaily Osman; Norzalina Zainudin; Zuroni Md. Jusoh; Fadilah Puteh (Penerbit Universiti Kebangsaan Malaysia, 2022)
Single–use plastics waste, when not properly managed and discarded, poses a threat to both the environment and human health. In the next 30 years, the global plastics waste crisis will exacerbate if the current consumption pattern and their production continue. The plastics crisis is seen as an anthropocentric problem that requires the understanding of consumer consumption patterns in order to encourage its alleviation. Thus, this paper proposes a conceptual framework to examine the predictors for adopting single–use plastics reduction activities among young urban consumers in Malaysia. Rather than assuming the homogeneity of the consumer’s single-use plastics reduction pattern, the current framework posits that different consumers are at different stages of behavioural readiness and adoption. It also explores the underlying factors and specific social referent groups at each stage using the integration of the Transtheoretical Model and Theory of Planned Behaviour. Consumer segmentation based on the theoretical integration could be used to create a more targeted behavioural change efforts that align with the characteristics and drivers of each stage. It is hoped that the present research can help to support efforts in reducing single-use plastics as outlined in the Malaysia’s Roadmap towards Zero Single-Use Plastics 2018-2030 policy.